إعادة تأهيل مدرسة وداد ناصر الدين - العيسة, ايناس; سلهب, بيان (جامعة بوليتكنك فلسطين - معماري, 2014)
أعدت هذه الدراسة كمقدمة مشروع تخرج لمشروع إعادة تأهيل مدرسة وداد ناصر الدين للحصول على درجة البكالوريوس في الهندسة المعمارية ، يهدف لحل مشكلة أزمة المرور و تواجد البسطات بمواقع عشوائية . و يشمل البحث بالدراسة و التحليل على عدة موضوعات تشمل دراسة كاملة و شاملة لمشروع إعادة تأهيل مدرسة وداد ناصر الدين ، و يحوي الفصل الأول مقدمة للمشروع و أهداف و وصف المشروع ، الفصل الثاني يتحدث عن لمحة تاريخية عن مركز مدينة الخليل التجاري و عن الأسواق التجارية ، الفصل الثالث يتحدث عن نظريات و خلفيات تاريخية عن الأسواق و إعادة التأهيل ، الفصل الرابع يتحدث عن الاسس التصميمية الأولية لعمل الأسواق الشعبية بالإضافة إلى تفصيل كامل للمعايير التصميمية لفراغات السوق ، الفصل الخامس يتحدث عن حالتين دراستين لمشاريع أسواق شعبية و تم إعادة تأهيلها موضحاً عناصرها بالتفصيل ، و الفصل السادس يتحدث عن تحليل موقع المدرسة الواقع في مركز مدينة الخليل أما الفصل السابع و الأخير يتحدث عن البرنامج العام للمشروع موضحاً المساحات التفصيلية لفراغات المشروع و تفصيل العلاقات الوظيفية بين فراغات المشروع . This study was prepared as a prelude to the draft of Graduation Project of Wedad Nasser El-Din School rehabilitation Project in Hebron to get a B.A.C degree in Architecture, Aims to solve the problem of traffic crisis and the presence of random stalls sites. The research includes the study and analysis on several topics including the full and comprehensive study of Wedad Nasser El-Din School rehabilitation Project management , and contains the first chapter introduction to the project and objectives and the description of the project , the second chapter Talking about a historical overview of the commercial center of the city of Hebron and for the commercial market ,the third chapter Talking about theories and historical backgrounds for markets and rehabilitation, the fourth chapter Talking about the the basics the initial design work for the popular markets in addition to the full detail of the design standards for the market spaces ,the fifth chapter Talking about the two studies for the projects and popular markets have been rehabilitated, explaining in detail its elements , The sixth chapter Talking about the analysis of the location of the school, located in the center of Hebron , either the seventh and last chapter Talking about the general program of the project, explaining the detailed spaces of the project and detailing the functional relationships between the spaces of the project.
no of pages 100,13986, معماري 18/2014 in the store